2012
DOI: 10.1111/j.1538-7836.2011.04606.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐gated P2X1 ion channels protect against endotoxemia by dampening neutrophil activation

Abstract: Summary.  Background:  In sepsis, extracellular ATP, secreted by activated platelets and leukocytes, may contribute to the crosstalk between hemostasis and inflammation. Previously, we showed that, in addition to their role in platelet activation, ATP‐gated P2X1 ion channels are involved in promoting neutrophil chemotaxis. Objectives:  To elucidate the contribution of P2X1 ion channels to sepsis and the associated disturbance of hemostasis. Methods:  We used P2X1−/− mice in a model of lipopolysaccharide (LPS)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…Specific pathogen-free homozygous P2X1 2/2 have been described previously. 12,13 All animal care and experimental procedures were performed as recommended by the European Community Guidelines (directive 2010/63/ UE) and approved by the Marseille Ethical Committee #14 ( protocol number: 27-28092012).…”
Section: Methodsmentioning
confidence: 99%
“…Specific pathogen-free homozygous P2X1 2/2 have been described previously. 12,13 All animal care and experimental procedures were performed as recommended by the European Community Guidelines (directive 2010/63/ UE) and approved by the Marseille Ethical Committee #14 ( protocol number: 27-28092012).…”
Section: Methodsmentioning
confidence: 99%
“…These two mechanisms are not mutually exclusive, and both might contribute to the exacerbation of tissue injury and increased lethality. Others investigators reported that P2X 1 receptor deficiency failed to protect against, and rather slightly increased, mortality in LPS-induced endotoxemia (49). The reasons for these discrepancies are not clear.…”
Section: /2mentioning
confidence: 97%
“…Although P2X1 currents are also relatively small in these cells (,100 pA/pF) (46,54), their physiological effects can be rather extensive. For example, P2X1 receptors promote neutrophil chemotaxis (46) and protect against endotoxemia by dampening neutrophil activation (35). In platelets, P2X1 amplifies the responses (e.g., aggregation and dense granule secretion) of many ligands (e.g., collagen, thrombin, and ADP) (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…P2X1 receptor regulates integrin activity in hematic cells, such as platelets (54), neutrophils, and monocytes (35), whereas in healthy eosinophils, P2X1 activation upregulates CD11b expression (23). The integrin a M b 2 is involved in eosinophil adherence-dependent function, including transmigration and degranulation (32,37,57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation